An approach to produce biochar from coffee residue for fuel and soil amendment purpose - Naruephat Tangmankongworakoon (International Journal of Recycling of Organic Waste in Agriculture)
Purpose This research aimed to produce biochar from coffee residues (CR) as well as to develop the guidelines for using it as a fuel and a soil amendment. Method Initial properties of coffee residues have been characterized before experimenting with a biomass kiln, designed for use in biochar production. By carbonization method, using biomass kiln at the temperature of 350â550 °C with 45 min of the reaction time. Results It was found that the biochar made from coffee residue (BCR) possessed a high heating value and fixed carbon (7360 cal/g and 77.77%) whereas it produced such a low amount of ash, moisture and volatile matter (6.18, 4.16 and 11.89%, respectively). The atomic ratio of H/C (0.71) and O/C (0.28) ratios of BCR were shown that were in the range of coal. Moreover, BCR showed adsorption of iodine (612.28). According to the analysis of the chemical properties of BCR, its pH, EC, Nitrogen, Phosphorus, Potassium, OM and C/N ratio were 9.9, 1.66 dS/m, 3.1, 1, 1.7, 19.5 and 28.9%, respectively. Conclusion From the results of this study, it can be concluded that BCR could be potentially used not only as an efficient source of the fuel production but also suitable material for soil amendment due to its direct contribution in nutrient absorption along with retardation of nutrient leaching, thereby helping improve the efficacy of nutrient use and increase crop yields.